POSITION AND PROTECTION OF INDIGENOUS PEOPLES IN INHABITING CUSTOMARY FORESTS - Shidqi, Muhammad Nabiel; Salsabila, Ghea Nisya; Kinanti, Shinta Cahyani; D. Putri, Dira Julia; siahaan, andre (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
The 1945 Constitution of the Republic of Indonesia requires the government to protect every citizen's rights, including indigenous peoples' rights in managing customary forests. This study explores the legal position of indigenous peoples in the use of customary forests and how the government safeguards the constitutional rights of indigenous peoples. This research uses a normative juridical approach focusing on theoretical aspects and legal principles. The study results show that indigenous peoples are legal subjects and owners of rights to customary forests. The government protects these rights by providing legal certainty through local regulations recognizing and protecting indigenous peoples. There are still many conflicts between Indigenous Peoples and the Government and companies that receive forest management permits from the Government. Forestry policies do not facilitate the management of forests. Centralized forestry policies cause overlapping conceptions of customary forests and state forests. The suggestion from this study is that the law should also be concerned with the Indigenous people so that the law protects them and irresponsible parties cannot sue them.